(untitled) (Global Journal of Medical Research, 2015)
Background and aim: Healthcare workers are often in contact with micro-organisms present in blood, saliva, laboratory samples and specimens which may potentially transfer infectious diseases. Use of methods to remove and or decrease the number of contaminants on instruments, samples and tabletops are of paramount importance in infection control. Important properties of a good disinfectant aside from the ability to kill microbes include being safe , noncorrosive or damaging to instruments, odorless, colorless, economical and eco-friendly. This study was done to assess effectiveness and longevity of 6% Hydrogen Peroxide-silver for disinfection prior to sterilization.